7P Marketing Strategy in the Perspective of Islamic Law: A Case Study on Motorcycle Spare Parts Sales at UD Agung - Arjuna, Arjuna; Harahap, Muhammad Ikhsan; Nurbaiti, Nurbaiti (Jurisprudensi: Jurnal Ilmu Syariah, Perundang-Undangan dan Ekonomi Islam, 2025)
Ideally, marketing strategies in Islam should be fair, honest, and transparent, avoiding any form of deception. However, in reality, many businesses focus more on competition without considering Sharia aspects. This study aims to analyze the implementation of the 7P marketing strategy at UD Agung in increasing motorcycle spare parts sales from an Islamic law perspective. The research uses a descriptive qualitative method through observation, interviews, and document analysis. The findings reveal that an integrated 7P strategy successfully increased sales by 35%, supported by product diversity, competitive pricing, effective promotions, e-commerce expansion, human resource development, business process improvements, and store renovations. From an Islamic law perspective, this strategy is generally in line with Sharia principles, particularly in price transparency and product quality. However, the promotional aspects need evaluation to avoid manipulation. This study concludes that a customer-oriented 7P strategy can enhance sales and customer loyalty while aligning with Islamic law if conducted ethically.